EFFECTIVENESS OF BETEL LEAF EXTRACT (Piper betle L) AS AN ANTIBACTERIAL AGENT FOR TREATING BACTERIAL INFECTIONS (Aeromonas hydrophila) IN KOI FISH BREEDS - Aslamiah; Istyadji, Maya; Yulinda, Ratna (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
Betel leaf has a long history of use in traditional medicine due to its natural antibacterial properties. This study focuses on the antibacterial effects of betel leaf (Piper betle) extract, particularly against Aeromonas hydrophila infections in koi fish. The research employs an experimental approach using a Completely Randomized Design (CRD) with four treatment groups, each repeated twice. The treatments consist of: a control group (Treatment K) without betel leaf extract, Treatment A with 5 ml of betel leaf extract, Treatment B with 10 ml of betel leaf extract, and Treatment C with 15 ml of betel leaf extract. The results of the study demonstrate the significant efficacy of betel leaf extract in promoting the healing of Aeromonas hydrophila-infected fish. This is evident from observations of reduced wound diameter in fish treated with betel leaf extract. In Treatment A (5 ml dose), noticeable wound diameter reduction begins in the fourth week. Treatment B (10 ml dose) shows similar progress with visible healing in the third week. Treatment C (15 ml dose) exhibits the most promising results, with wound diameter reduction or fading evident as early as the second week. Survival rates are recorded as follows: Treatment K – 50%, Treatment A – 65%, Treatment B – 75%, and Treatment C – 90%. These findings underscore the potential of betel leaf extract as an effective antibacterial remedy in combating Aeromonas hydrophila infections in koi fish.